Advances in Neural Networks - ISNN 2014 11th International Symposium on Neural Networks, ISNN 2014, Hong Kong and Macao, China, November 28 -- December 1, 2014. Proceedings - Zeng, Zhigang; Li, Yangmin; King, Irwin (Theoretical Computer Science and General Issues,, 2014)
The LNCS volume LNCS 8866 constitutes the refereed proceedings of the 11th International Symposium on Neural Networks, ISNN 2014, held in Hong Kong and Macao, China on November/ December 2014.   The 71 revised full papers presented were carefully reviewed and selected from 119 submissions. These papers cover all major topics of the theoretical research, empirical study and applications of neural networks research, with particular focus on analysis, modeling, and applications.